2019
DOI: 10.3389/fpls.2019.00368
|View full text |Cite
|
Sign up to set email alerts
|

Soil Enzyme Activity in Soils Subjected to Flooding and the Effect on Nitrogen and Phosphorus Uptake by Oilseed Rape

Abstract: Waterlogging presents one of the greatest constraints for agricultural crops. In order to elucidate the influences of waterlogging stress on the growth of oilseed rape, a pot experiment was performed investigating the impact of waterlogging on nitrogen (N) and phosphorus (P) accumulation in oilseed rape, and mineral N and available P profiles and enzyme activities of soils. The experiment included waterlogging treatments lasting 3 (I), 6 (II), and 9 (III) days, and a control treatment without waterlogging (CK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Soil enzymes are important bioactive proteins that participate in soil nutrient cycling and indicate soil fertility and soil environmental quality [28,46]. Urease is involved in soil nitrogen cycling and exerts an important role in improving soil quality and fertility [30,47]. Phosphatase plays an important role in hydrolyzing soil organic phosphate into inorganic phosphate, which can meet the phosphorus requirement of plants [31].…”
Section: Discussionmentioning
confidence: 99%
“…Soil enzymes are important bioactive proteins that participate in soil nutrient cycling and indicate soil fertility and soil environmental quality [28,46]. Urease is involved in soil nitrogen cycling and exerts an important role in improving soil quality and fertility [30,47]. Phosphatase plays an important role in hydrolyzing soil organic phosphate into inorganic phosphate, which can meet the phosphorus requirement of plants [31].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the input of N fertilizer while maintaining yields of rapeseed will, therefore, likely entail improving the NUE of rapeseed. Furthermore, rapeseed is sensitive to various environmental stresses, such as macronutrient deficiencies, waterlogging and drought stresses, these will lead to the nutrients imbanlance, influence the N metabolism or other metabolic pathways, finally suppress the growth and yield of rapeseed [20][21][22][23][24][25]. It's necessary to understand the adaptive patterns of NRT2 family genes in response to these stresses which commonly appeared in the production of rapeseed.…”
Section: Introductionmentioning
confidence: 99%
“…However, when expressed in relation to microbial biomass carbon or soil organic carbon (i.e., specific enzyme activity), the authors observed an increase due to rice cultivation [99]. Thus, the lower activities of beta-glucosidase and phosphatase in rice-cultivated soils in both Umbeluzi and Chokwe suggest that rice cultivation, along with the associated reductive effect on nutrient availability, contribute to a reduction in the stoichiometry of these enzyme activities involved in the mineralization of carbon and phosphorus [95,97,98,100,101]. In the case of urease, we observed higher mean activity in the rice-cultivated field in Chokwe compared to the corresponding fallow field (5YF), but the opposite was true for Umbeluzi.…”
Section: Discussionmentioning
confidence: 99%